Penerapan Model Pembelajaran Kooperatif Tipe STAD Untuk Meningkatkan Hasil Belajar Siswa - Sihombing, Evi Ariyanti Marlina; Surya, Edi; Fauzi, Kms. Muhammad Amin (Pusdikra Publishing, 2024)
STAD type cooperative model. The subjects in this research were 30 class VII students of SMP Negeri 4 Pantai Labu and the object of this research was to see the learning outcomes of the learning process carried out. 2) the effectiveness of Learning Design Development using the STAD Type Cooperative model developed on students' mathematical abilities. The learning design developed (STAD Type Cooperative Model, has met the level of validity with a reliability coefficient of 0.790. Based on data obtained from testing the learning design, it is known that: 1) the design developed has been able to meet the effectiveness of the learning process, 2) Obtained learning outcomes good for students' mathematical abilities. Based on the research results, it can be concluded that all aspects determined to declare a design development product valid and effective have been fulfilled, so the development cycle to obtain a valid and effective learning design has ended. Improved student learning outcomes can be seen from the results of students' mathematical ability tests on flat plane material. In the trial, there were 26 students (86.67%) out of 30 students who took the posttest with a level of student mathematical ability in the minimum category B. This shows that the percentage of students who have completed their mathematical abilities on flat plane material has increased from trial I to trial II, namely 16.67%.